Challenges Facing Indian Democracy in the Digital Age: Cyber Security and Election Integrity (London Journal of Research In Humanities and Social Sciences, 2024)
In the digital age, Indian democracy faces significant challenges that threaten the integrity of its electoral processes and the security of its cyberspace. This paper explores two critical issues: cybersecurity vulnerabilities and threats to election integrity within the context of India’s evolving digital landscape. It examines the multifaceted nature of cyber threats, ranging from data breaches and misinformation to targeted cyber-attacks on electoral infrastructure, which collectively pose a substantial risk to the sanctity of democratic processes. Additionally, the paper delves into the complexities introduced by digital voting systems, social media influence, and the role of artificial intelligence in shaping political narratives. By analyzing recent incidents and existing governmental frameworks, the study highlights the urgent need for robust, adaptive strategies to safeguard democracy against these digital age challenges. The objective is to provide a comprehensive overview of the current threats and propose strategic measures to enhance resilience in India’s digital and democratic spheres. Through this exploration, the paper aims to contribute to the ongoing discourse on maintaining and strengthening democratic practices in the face of growing digital challenges.
Keywords: Nikolai Marr; glottogenesis; labor; tool of labor; manual (linear; kinetic) language; sound language.; Convergence; Research Creation; Interdisciplinarity; Semillero.; students; knowledge; drug abuse; Information; sources; undergraduate; communication; electronic; Technologies; cybersecurity